HIGHER EDUCATION LEARNERS' ATTITUDES TOWARDS EMERGENCY ONLINE INSTRUCTION DURING COVID-19 PANDEMIC: THE CONTEXT OF TURKEY - Mohammadreza Valizadeh; Fatemeh Soltanpour (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
This mixed-methods study aimed at investigating the Turkish higher education learners' attitudes towards Emergency Online Teaching (EOT) under the Covid-19 pandemic in order to discover the benefits and drawbacks of it. The participants were 251 higher education learners who received the EOT during the Covid-19 crisis in Turkey. Both qualitative and quantitative data were gathered by means of a questionnaire in August 2020. Quantitative data were obtained via closed-ended questions with the response on a Likert-scale format. Qualitative data were acquired through open-ended questions. The results showed that the hurried shift to an online instruction by universities in Turkey was not fully satisfactory and the majority of the respondents (74.1%) preferred face-to-face learning to the online format, however, the participants also stated that they felt safer during this pandemic disease thanks to the availability of distant online education. The drawbacks they mentioned included inadequate technological infrastructure or facilities, lack of sufficient teacher-student and peer interaction, lack of learners' attention and concentration, tediousness of online lessons, learners' inadequate engagement in class activities, as well as the absence of comprehensive assessment procedure.